(untitled) (NAU Journal of Technology and Vocational Education, 2024)
This study ascertained extent of application of financial accounting information in the management of tertiary educational institutions in South-East Nigeria. Two research questions guided the study and two null hypotheses were tested. Descriptive survey research design was adopted for the study. The population comprised 1535 account officers in all the 26 public tertiary educational institutions in South East, Nigeria. A sample of 317 account officers were sampled using Taro Yamane’s formula through proportionate sampling technique. The instrument for data collection was a 48-item structured questionnaire. The instrument was validated by three experts. To determine the internal consistency of the instrument, Cronbach Alpha was used and obtained the reliability co-efficient values of 0.91 and 0.83 for clusters B1 to B2 with an overall co-efficient value of 0.87. Mean and standard deviation were used to answer the research questions, while ANOVA was used to test the null hypotheses at 0.05 alpha levels. The findings of the study revealed that account officers moderately applied cash flow statements and fixed assets accounts in the management of tertiary educational institutions in South-East Nigeria. Account officers’ institution type significantly influenced their mean ratings on the extent of application of cash flow statements in the management of tertiary educational institutions in South-East Nigeria, but did not significantly influence their mean ratings on the extent they applied fixed assets accounts in the management of tertiary educational institutions. The study concluded that financial accounting information in the management of tertiary educational institutions were not widely applied in South-East Nigeria. It was recommended among others that administrator/management of tertiary educational institutions should prepare financial accounting information and use same in their management of the institutions to prevent fraud. This will help in combating menace fraud in the institutions. Thus, the regular extent of application of financial accounting information should be encouraged.